UNODA Occasional Papers No. 42 - United Nations Office for Disarmament Affairs (United Nations, 2024)
The integration of artificial intelligence (AI) into military applications, such as weapon systems, decision-support tools, and various other tasks, poses opportunities and challenges to international peace and security. Military applications of AI can exacerbate and amplify existing risks and could also lead to new unintended consequences. Rapid developments in this technological domain have outpaced the development of guardrails to mitigate such risks. This publication aims to enhance the international community’s understanding of the governance of AI in the military domain. It outlines the opportunities and risks associated with military applications of AI, highlights areas of contention within the expert and diplomatic communities, and offers policy recommendations and options for its multilateral governance.